DFT Study on the Gas Phase Reactions of Pt+ and Pt with CO2 - Wang, Chuan-Feng; Dai, Guo-Liang (Asian Journal of Chemistry, 2013)
In order to better understanding the mechanism of third-row metal reacting with CO2, the reactions of Pt+ cation and Pt atom with CO2 have been investigated at B3LYP level of theory. The minimum energy reaction path is found to involve the spin inversion in the different reaction steps. This potential energy curve-crossing dramatically affects reaction exothermic. The present results show that the reaction mechanism is insertion-elimination mechanism along the C-O bond activation branch. All theoretical results not only support the existing conclusions inferred from early experiment, but also complement the pathway and mechanism for this reaction.